New Agricultural Management Technologies by Farmers in India - Amar Shankar, Nandini Datta (International Journal of Modern Agriculture, 2021)
Agricultural progress is seen as one of the major field in which one can outlive poverty in any of the developing country. Though the acceptance rate for agriculture is increasing with every brink of time passing. Agricultural planning is fraught with danger and uncertainty. After analyzing the deep roots of the agricultural risks in the country which usually stands out to be the several utility theories and risk analysis and their diversion are counted to be affirmative and strongly dependent on the climatic changes and all the necessary aspects of crop yielding and deformation and soil erosion and many more financial, ecological aspects to keep track of it. A Farmer is usually expected to have a mixed gathering marketing strategies and portfolio are expected to minimize the risks and have maximum profit returns from any type of yields. This paper examines and provides different methods to calculate the current situation of the knowledge provided by the producers, cultivators for managing price and risk revenues for different agricultural farming commodities, it also put different agricultural managing technologies tactics in several developing countries into consideration. This paper also put the reviews of the prior studies into for better technologic understandings for their adoption. This study also enlightens economic, institutional, technological and specific style farming style adaption of technologies. Farmers’ views of emerging technologies may be used in future acceptance studies, expanding the number of variables used.